Botanični in naravovarstveni pomen travnikov združbe Danthonio-Scorzoneretum villosae Ht. & H-ić (56)58 nad Rakitovcem v Čičariji (jugozahodna Slovenija) - Kaligarič, Mitja (Annales. Series historia naturalis, 1997)
The article deals with the vegetation of dry meadows mown traditionally in themontane belt above Rakitovec (Čičarija, Slovenia). They belong to the assoc. Danthonio-Scorzoneretum villosae Ht. & H-ić (56)58 subas rhinanthetosum glacialis Kaligarič & Poldini 97. This subass. ecologically means the nucleus of the association (typical, the richest form with characteristic species), and at the same time the transition between the Istra-Kvarner (from where the assoc. was described) and the Karst race of this association.The geoelemental composition of the association highly represents Illyrian, Mediterranean-montane, and more mesophilous (euro-Siberian, Eurasian, and European) elements to the detriment of thermophilous Mediterranean elements. In the stands above Rakitovec we find some rare and threatened species in the flora of Slovenia: Serratula Iycopifolia, Serratula radiata, Delphinium fissum, Nepeta pannonica and Scorzonera hispanica, mentioned in the article. We belive that estimate these meadows are highly threatened, as they depend on extensive moving that is to be interrupted soon. We therefore suggest that the Ministry of Environment as well as non-governmental organisations contribute, with subsidies to the extensive moving
Keywords: Čičarija; Ćićarija; flora; Rakitovec; rastlinstvo; travniki; vegetacija